Konflik Kewenangan Pemerintah dan Persatuan Sepakbola Seluruh Indonesia Menyelesaikan Sengketa Pemain Sepakbola - Ferry Anggriawan (University of Merdeka Malang, 2018)
This study aims to examine conflicts of authority of the Government and PSSI in resolving disputes of professional football players that occur outside of football matches.Conflicts of authority occur when PSSI resolves the dispute of professional football players who are inconsistent with positive law in Indonesia. This research resulted in conclusion, among others; the first legal position of PSSI authority when settling the dispute of professional soccer player is not in accordance with the purpose of law, because it does not meet one element of legal certainty, dispute resolution mechanism applied by PSSI not in accordance with the doctrine of transnational sport law that refers to FIFA, justice and benefit; second impact if PSSI resolve the dispute with reference to transnational sports law system is the authority of PSSI is contrary to positive law in Indonesia, among others Article 59 paragraph 3 Law No. 17 of 2013 on Social Organization, Article 121 paragraph 1 and 2 Government Regulation No. 16 Year 2007 on the Implementation of Sports.How to cite item: Anggriawan, F. (2018). Konflik Kewenangan Pemerintah dan Persatuan Sepakbola Seluruh Indonesia Menyelesaikan Sengketa Pemain Sepakbola. Jurnal Cakrawala Hukum, 9(2), 151-159. doi:https://doi.org/10.26905/idjch.v9i2.2730